Efektivitas Platform Digital Sebagai Media Penguatan Nilai Sosial Di Kalangan Pelajar Sekolah Menengah Pertama - Christian Sugiyanto; Michael Rendy Sutoyo (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
It has transformed the way that students can access information and how they can engage in social activities, effectively making digital platforms such as YouTube and TikTok the norm in their lives. However, the fact remains that these platforms have not been optimized for the education of social values. This study aims to analyze how effectively a digital platform is used as a medium for strengthening social values among junior high school (SMP) students. Mixed methods with a sequential explanatory design were used. 120 students responded to the quantitative survey, and 12 students were interviewed qualitatively to get their experiences on accessing socially valuable digital content. This study establishes that YouTube is the most capable platform for transmitting value concepts such as empathy, tolerance, and cooperation by means of visual and narrative content. The study reports a strong, positive correlation between the extent of exposure to social content and change in students' social attitudes (r = 0.604, p < 0.001), with regression analysis further explaining 36.1% of variation in attitude change as a function of the intensity of social content access. This study is novel in its concentration on the junior high school age group, a largely neglected area in the field, and in taking an integrative approach to measuring how digital platforms impact student attitudes. On the practical side, the conclusions of this study propose character education strategies in digital media that are contextualized for the current generation of students.